2022
DOI: 10.31925/farmacia.2022.4.2
|View full text |Cite
|
Sign up to set email alerts
|

ANALGESIC ED50 DICLOFENAC-EUGENOL COMBINATION EFFECT ON PROINFLAMMATORY CYTOKINES – IL-1β, IL-6, TNFα AND MAPKs – IN RAT MUSCLE

Abstract: Inflammation is a typical response to a wide variety of stressors, including xenobiotics, which can develop a prolonged, severe, and inappropriate inflammatory response that can lead to events at the molecular level degenerating into adverse effects. The objective of the study was to evaluate the effect of ED 50 diclofenac-eugenol (DFC+EUG) combination on proinflammatory cytokines (IL-1β, IL-6, TNFα and MAPKs) in rat muscle. The treatments as well as the control solutions were administered in the gastrocnemius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It has been previously shown that administration of diclofenac induces an increase in the expression of IL-1β between 3 and 12 hours after administration [25], in the case of eugenol + diclofenac there was also an increase in IL-1β but the dose of the drugs was 20 times lower [26]. Our results shown here are focused on the acute antinociceptive efficacy of both drugs in combination.…”
Section: Resultsmentioning
confidence: 58%
“…It has been previously shown that administration of diclofenac induces an increase in the expression of IL-1β between 3 and 12 hours after administration [25], in the case of eugenol + diclofenac there was also an increase in IL-1β but the dose of the drugs was 20 times lower [26]. Our results shown here are focused on the acute antinociceptive efficacy of both drugs in combination.…”
Section: Resultsmentioning
confidence: 58%